125 Characterising sleep and fatigue in patients with primary mitochondrial disease. (29th July 2019) - Wools, Christine; Sue, Carolyn; Cistulli, Peter; Davis, Ryan
Abstract : Introduction: Fatigue is common in patients with primary mitochondrial disease (PMD). There has been little prospective research into sleep pathology in these patients and assessment of scontributory factors to fatigue. Methods: Patients with PMD were prospectively assessed with overnight polysomnography in addition to measures of fatigue, muscle fatiguability, disease severity, sleep propensity and depression. Results: 16 patients participated, 15 completing inpatient polysomnography. Obstructive sleep apnoea (OSA) was common (53%), affecting 5/9 females (56%) and 3/6 males (50%), although most cases were mild in severity. There was a trend to higher incidence of OSA in older patients but not other traditional risk factors, nor presence of myopathy. The Epworth Sleepiness Scale (ESS) was the best predictor of OSA, although not reaching significance. Fatigue was common, with 81% of patients having significant fatigue on the Fatigue Severity score and 69% on the Fatigue Impact Scale. The two scores correlated well (r =0.85, p 0.01). The mean 5 times sit to stand time of 16 seconds was significantly higher than community normals (p 0.04), demonstrating muscle fatiguability, not isolated to patients with myopathy. Conclusion: OSA is common in patients with PMD, although mostly mild in severity. ESS likely remains a relevant tool in screening patients when considering overnight polysomnography to investigate fatigue in these patients. OSA does not explain the high prevalence of fatigue, with other factors including depressive symptoms, important considerations.